Inter-hospital transfers and door-to-balloon times for STEMI: a single centre cohort study - Forsyth, René; Sun, Zhonghua; Reid, C.; Moorin, R. (Science Press, 2020)
Background Key performance indices such as door-to-balloon times have long been recognized as quality metrics in reducing time to care for patients with acute coronary syndromes (ACS). In the situation where patients do not present to a facility capable of 24/7 percutaneous coronary interventions (PCI) delays in time to therapy can exceed the recommendation of 90 minutes or less. This study aimed to evaluate the impact of transfers on performance indices for patients diagnosed with ST-segment elevation myocardial infarction (STEMI). Methods Over a seven month collection period, all patients presenting with symptoms suggestive of ACS and admitted for PCI were studied. Patients were divided into dichotomous groups of direct presentations or transfers from a secondary non-PCI capable hospital with key times recorded, including symptom-onset, first hospital and PCI-capable hospital arrival and balloon inflation times to evaluate time of treatment for STEMI patients. Results Of the 87 patients diagnosed with STEMI, transferred patients experienced statistically significant delays in symptom-onset to the PCI-capable hospital (PCI-H) arrival (215 vs. 95 min, P < 0.001), symptom-onset to balloon inflation (225 vs. 160 min, P = 0.009) and first hospital arrival to balloon inflation times (106 vs. 56 min, P < 0.001). Only 28% (n = 9) of transferred patients underwent balloon inflation within 90 minutes from first hospital arrival, while 60% (n = 19) did within 120 minutes, although all received balloon inflation within 90 minutes from arrival at the PCI-H. After controlling for confounding factors of socio-economic status, presentation date/ time and diagnostic category, transferred patients experienced an average 162% longer delays from symptom-onset to PCI-H door arrival, and 98% longer delays in symptom-onset to balloon inflation; compared to patients who present directly to the PCI-H. No statistically significant differences were noted between transferred and direct patients when measured from PCI-H door-to-balloon times. Conclusions This study shows that transferred patients experience a greater overall system delay, compared to patients who present directly for PCI, significantly increasing their time to treatment and therefore infarct times. Despite the majority of transfers experiencing pre-hospital activation, their treatment hospital arrival to balloon times are no less than direct presenters after controlling for confounding factors, further compounding the overall delay to therapy.